Theology is for preaching : biblical foundations, method, and practice - Kuhn, Chase R.; Grimmond, Paul (Studies in historical & systematic theology., 2021)
"Is it right to "just preach the text"? Why do we preach and do theology? How do we relate them? And how do they relate to God's word? Theology Is for Preaching helps preachers with theology and theologians with preaching. Though diverse in contexts and disciplines, the contributors share a commitment to equipping the saints to "rightly handle the word of truth." Through essays on foundations, methods, employing theology for preaching, and preaching for theology, this volume will equip preachers and theologians to engage deeply with the text of the Bible and communicate its meaning with clarity."--